Massive black hole remnants of the first stars and their significance in present-day galactic halos - Islam, R; Islam, Ranty (2003)
We investigate the possibility that present-day galaxies and their dark matter halos contain a population of massive black holes (MBHs) that form by hierarchical merging of the black hole remnants of the first stars in the Universe. Some of the MBHs may be large enough or close enough to the centre of the galactic host that they merge within a Hubble time. We estimate to what extent this process could contribute to the mass of the super-massive black holes (SMBHs) observed in galactic centres today. The relation between SMBH and galactic bulge mass in our model displays the same slope as that found in observations. Many MBHs will not reach the centre of the host halo, however, but continue to orbit within it. In doing so MBHs may remain associated with remnants of the satellite halo systems of which they were previously a part. Using a semi-analytical approach that explicitly accounts for dynamical friction, tidal disruption and encounters with galactic disks, we follow the hierarchical merging of MBH systems and their subsequent dynamical evolution inside the respective host halos. In this context two types of dynamical processes are examined in more detail. We predict the mass and abundance of MBHs in present-day galactic halos and also estimate the MBH mass accretion rates considering two different accretion scenarios. On this basis we determine the bolometric, optical and X-ray luminosity functions for the accreting MBHs using thin disk and advection dominated accretion flow models. Our predicted MBH X-ray emissions are then compared with observations of ultra-luminous X-ray sources in galaxies. We find that the slope and normalisation of the predicted X-ray luminosity function are consistent with the observations. We also estimate the rate of gravitational wave events received from MBH mergers across all redshifts. At the end of their lives the first stars may explode in supernovae that are associated with gamma ray bursts (GRBs). Provided these are in principle detectable we have estimated the expected rate of events observed.